Kesadaran siswa sekolah dasar di Balikpapan Selatan dalam mitigasi bencana tanah longsor: studi kasus berbasis kuesioner - Andi Marini; Giat A. Sabalarang; Adam P.; Rifa’I M. N Aditya; Teguh H.; Deffy Nur A.; Rizkiah Zalzabilah; Ummar Badaruddin; Muhammad Yasir Indrawan; Achmad Ray B. (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Landslide mitigation is a crucial effort in reducing the negative impacts of disaster, particulary ini high-risk aras such as South Balikpapan. This study aims to evaluate the awareness level of elementary school in South Balikpapan regarding landslide mitigation using a questionnaire covering three main aspects: understanding the causes of landslide, evacuation steps, and mitigation procedures. Data were collected from 578 students in grades 4-6 and analyzed descriptively. The result show that most students have a good understanding of the causes of landslide (70%), but only 35% of students understand the correct evacuation steps. Mitigation socialization is also lacking, with 73% of students stating they have never received formal socialization in school. This study recommends conducting regular disaster simulation and integrating mitigation materials into the curriculum to enhance student awareness. These findings provide strategic insight for educational institutions and stakeholders in landslide mitigation efforts.